An investigation of the molecular-level mineral chemistry of metal-bearing pyrite and its electrochemical behaviour under flotation related conditions - Babedi, Lebogang (Stellenbosch : Stellenbosch University, 2023)
Thesis (MSc)--Stellenbosch University, 2023.